2019
DOI: 10.1108/dprg-09-2018-0050
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art and adoption of artificial intelligence in retailing

Abstract: Purpose In the most abstract way, artificial intelligence (AI) allows human work to be shifted toward technological systems that are currently not fully capable. Following this, the domain of retail can be sketched as a natural fit for the application of AI tools, which are known for their high proportion of human work and concurrent low profit margins. This paper aims to explore the current dissemination of the application of AI within the industry. The value-added core tasks of retail companies are examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 35 publications
2
65
0
Order By: Relevance
“…A notable example is Amazon, with its model of the Amazon Go store. Robots used for sales support in Amazon Robotics, Cisco, Ocado, and Softbank are more compatible with current store models (Weber & Schütte, 2019).…”
Section: Customer Service and Payment Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…A notable example is Amazon, with its model of the Amazon Go store. Robots used for sales support in Amazon Robotics, Cisco, Ocado, and Softbank are more compatible with current store models (Weber & Schütte, 2019).…”
Section: Customer Service and Payment Managementmentioning
confidence: 99%
“…AI is also used to determine how many products of each commodity should be stored in various warehouses depending on the local warehouse, season, area and major cities (Weber & Schütte, 2019). Then accordingly, AI adjusts the quantities of optimal stock.…”
Section: Inventory Optimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that once the technology adoption process is successful, the impact on the business can be very important. For example, in the retail industry, a lot of champions made a significative growth by adopting IA like Amazon and Walmart [10].…”
Section: Challenges Facing Ai Integration and Adoptionmentioning
confidence: 99%
“…This level of awareness suggests that the awareness and, ultimately, the adoption of AI solutions in the Loire wine industry is at a very early stage. It can, however, be assumed that this is not necessarily representative of the wine industry either in France or internationally, given that previous research observed variances in the adoption of AI within a specific sector (Weber & Schütte, 2019). This exploratory study aims to identify which factors enable or inhibit the wine grower's intention to adopt AI technology.…”
Section: Introductionmentioning
confidence: 99%